Un'azione edu-formativa «smart» come via italiana alla città intelligente: mediateca e cultura digitale - Luca Luciani (LED Edizioni Universitarie, 2014)
A Smart Educational Action as the Italian Pat to the Smart City: The Multimedia Public Library and Digital Culture Although the term «smart city» is increasingly used today, it is open to different interpretations and uses. Much like an increasing fashion that is easy to adopt, the smart city is being increasingly proclaimed, proposed and considered a goal by policymakers. Many administrative actions and applications are called «smart», but what is a «smart city» exactly? When can a city actually be considered smart? What is the relationship between the «smartness» of its technological-organizational systems of social life, of its environment or territory and of its citizens' intelligence? Considering the development and evolution of the modern city, is there a relationship between intelligence and creativity? Through the answers to these questions, the result of a logical-consequential theoretical analysis, and with regard to the critical acquisition and spreading of a digital culture, this contribution aims to put forward and support the value linked to creating a widespread network of multimedia public libraries, proposed as a cornerstone for actually achieving a smart city. This action must not be delayed in Italy seeing as it significantly lags behind other European and more economically advanced countries in this regard. Italy is sorely lacking in this kind of library with its far-reaching cultural benefits that can potentially enhance human socio-creative development of «digital intelligence».